The Influence of Liquidity Ratio (CR), Solvency Ratio (Dar), Activity Ratio (TATO), And Profitability Ratio (ROI) On Stock Prices at PT. Various Mines Tbk. Period 2007-2021 - Rahmat, Azis Sofyan; Ganar, Yulian Bayu (Fin Sinergy: Jurnal Manajemen Keuangan, 2024)
This research aims to determine the effect of liquidity ratios, solvency ratios, activity ratios and profitability ratios on PT share prices. Aneka Tambang TBK for the period 2007-2021. The sampling technique used was non-probability sampling. The liquidity ratio uses the Current Ratio, the solvency ratio uses the Debt to Asset Ratio, the activity ratio uses Total Asset Turnover, and the profitability ratio uses Return on Investment. And for company share prices, use the closing share price at the end of each year. The analytical method used is multiple linear regression analysis. The research results simultaneously show that the variables CR, DAR, TATO, & ROI have a significant effect on stock prices. The partial research results show that CR has no significant effect on stock prices, DAR has no significant effect on stock prices, and TATO has no significant effect on stock prices. Meanwhile, ROI has a significant effect on share prices.